Colorado Community College student perceptions of higher-education affordability: a phenomenological study - Rosner-Salazar, Ari Senghor, author; Kuk, Linda, advisor; Quick, Don, committee member; Stewart, Malcolm, committee member; Voorhees, Richard, committee member (Colorado State University. Libraries, 2018)
Using a phenomenological method, this study explored the higher-education affordability perceptions of a purposively-collected group of 19 students at the pseudonymous Crestview Community College (CCC) in Colorado. The defining themes of the study were: (a) knowledge of the College Opportunity Fund (COF) program and perceptions of higher-education affordability in the Colorado context, (b) how participants learned about and implemented college selection, financing, and success strategies, (c) family finances and their impact on work and college decisions, (d) participant views on the financial aid process, and (e) benefits of attending college. The findings were: (a) the COF was not viewed as a significant source of support or well-understood as the State of Colorado's contribution to college students, (b) participants described difficulty in high school learning and implementing a college selection and financing strategy with some mitigation of those failures by key adults in their lives, (c) CCC was viewed as the default college choice because of price, location, dual credit experience, and peer recommendations, (d) family structural and financial context strongly influenced participants' perceived options and decisions regarding college selection and work, (e) participant perspectives on federal financial aid and college affordability varied drastically between Pell Grant recipients and non-recipients, (f) participants uniformly held a negative perception of student loans, and (g) participants were motivated to stay in college by hope of occupational and financial benefits and discouraged by fear of debt and post-graduation joblessness.
Keywords: affordability; Colorado; tax; COF; access; stipend